2023
DOI: 10.3808/jeil.202300114
|View full text |Cite
|
Sign up to set email alerts
|

Role of Informal Waste Workers for Sustainable Waste Management in Nigeria and Nepal

A. Khanal,
A. R. Aroyehun,
A. Garba
et al.

Abstract: Informal waste workers (IWWs) play a vital role in recovery, disposal and recycling of waste materials. This study examines the current solid waste management practices in Nigeria and Nepal, with a particular focus on the roles of IWWs in effective waste management. Through comprehensive secondary literature reviews, including journal databases, books, reports, and websites, this study highlights the inadequate solid waste management systems in both countries, resulting in limited reuse of generated waste. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…The International Labour Organization (2023) reported that almost 40 per cent of people working in the informal sector in 2019 were in roles related to waste management and sanitation, of which 45 per cent were women and 38 per cent men (there were significant differences in these percentages among regions). In waste management policymaking there is a need to recognise the roles and respond to the voices of waste workers in the informal economy (UNDP 2022, b; Chen 2023; Khanal et al 2023).…”
Section: %-25%mentioning
confidence: 99%
“…The International Labour Organization (2023) reported that almost 40 per cent of people working in the informal sector in 2019 were in roles related to waste management and sanitation, of which 45 per cent were women and 38 per cent men (there were significant differences in these percentages among regions). In waste management policymaking there is a need to recognise the roles and respond to the voices of waste workers in the informal economy (UNDP 2022, b; Chen 2023; Khanal et al 2023).…”
Section: %-25%mentioning
confidence: 99%
“…The government and private companies collect waste in urban areas of Nepal, with private waste management companies dominating the industry. Despite this, there is still much work to be done to improve waste management in Nepal, including implementing a waste tracking system and studying the role of the informal sector more closely (Khanal et al, 2023b).…”
Section: Current Solid Waste Management Practicesmentioning
confidence: 99%